Leishmania mexicana infection of the eyelid in a traveler to Belize - Joseph M. Vinetz (Brazilian Journal of Infectious Diseases)
A 50 year-old man, a United States resident, presented in Texas with a violaceous non-ulcerating lesion, involving the entire lower eyelid. The patient had traveled to a jungle area of Belize several hours drive from the capital city. Leishmania mexicana was isolated. The lesion only partially resolved after an initial course of sodium stibogluconate, requiring retreatment. At two years of follow-up, there was no relapse. The parasite isolated from the patient caused a progressive, non-ulcerating lesion in an experimental mouse footpad infection. This is an unusual case of cutaneous leishmaniasis in a traveler. Travelers must be educated about personal protective measures to prevent exotic infections acquired during travel.